2001
DOI: 10.1191/096120301682430212
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic capillary changes and manifestations of connective tissue diseases in patients with primary biliary cirrhosis

Abstract: The objective of this study was to investigate the presence of nailfold capillary abnormalities and extrahepatic signs of connective tissue disease in patients with primary biliary cirrhosis (PBC), as compared to patients with other chronic liver diseases. We evaluated 22 patients with PBC and 15 patients with other chronic liver diseases as a control group. Nailfold capillaroscopy was performed by two observers blinded to clinical findings using a Wild M3 stereomicroscope with an Intralux 5000 Volpi cold ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The use of nailfold capillaroscopy in patients suspected of having connective tissue disease may be a useful indicator. 56 In conclusion, patients with PBC and SSc had a lower rate of liver transplantation and a lower rate of liver related deaths, with a slower rate of bilirubin increase with respect to patients with PBC alone. However, these differences were not due to earlier SSc related deaths.…”
Section: Discussionmentioning
confidence: 77%
“…The use of nailfold capillaroscopy in patients suspected of having connective tissue disease may be a useful indicator. 56 In conclusion, patients with PBC and SSc had a lower rate of liver transplantation and a lower rate of liver related deaths, with a slower rate of bilirubin increase with respect to patients with PBC alone. However, these differences were not due to earlier SSc related deaths.…”
Section: Discussionmentioning
confidence: 77%
“…A recent report from EUSTAR has suggested that the early diagnosis of SSc should be based in three domains: skin (puffy fingers/puffy swollen digits turning into sclerodactily), vascular (Raynaud's phenomenon, abnormal capillaroscopy with scleroderma pattern) and laboratory (testing for ANA in general and ACA and ATA in particular) domains [162]. In addition, it has been suggested that videocapillaroscopy should be incorporated in the diagnostic algorithm of PBC patients with suspected SSc [163]. Besides capillaroscopy, assessment of lung function by spirometry and echocardiography should be considered in the group of PBC patients diagnosed with SSc [26].…”
Section: Clinical Significance Of Anti-centromere Antibodies In Pbc Pmentioning
confidence: 98%
“…Experimental and clinical observations suggest that endothelial dysfunction is present in PBC patients. One study found nailfold videocapillaroscopy abnormalities in 91% of patients with PBC, and 54% had capillary alterations characteristic of SSc (Fonollosa et al, 2001). Eleven out of the 22 PBC patients (50%) had extrahepatic signs of connective tissue disease with most being related to SSc, while patients with other types of chronic liver disease did not present with rheumatic manifestations (Fonollosa et al, 2001).…”
Section: Screening and Diagnosis Of Pbc In Ssc Patients And Vice Versamentioning
confidence: 99%
“…One study found nailfold videocapillaroscopy abnormalities in 91% of patients with PBC, and 54% had capillary alterations characteristic of SSc (Fonollosa et al, 2001). Eleven out of the 22 PBC patients (50%) had extrahepatic signs of connective tissue disease with most being related to SSc, while patients with other types of chronic liver disease did not present with rheumatic manifestations (Fonollosa et al, 2001). The high prevalence of nailfold capillary abnormalities characteristic of SSc in patients with PBC, and correlation with sclerodermal manifestations, suggests that this capillaroscopic finding could be a useful indicator to investigate rheumatic manifestations in these patients (Fonollosa et al, 2001).…”
Section: Screening and Diagnosis Of Pbc In Ssc Patients And Vice Versamentioning
confidence: 99%
See 1 more Smart Citation